Pengaruh Terpaan Media Terhadap Partisipasi Politik Dalam Pilkada Dki Jakarta 2017 - Umar Halim; Kurnia Dyah Jauhari (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
The political participation of the people is one of the indicators of democracy in every country. More and more citizens are involved the better, as it shows citizens following and understanding the political problems. This study uses the Stimulus-Response (S-R) theory. The purpose of this study is to examine whether the hypothesis that there is a positive and significant influence between media exposure to the level of political participation among the people of South Jakarta. This research used quantitative methods, with data collection techniques spreading questionnaires to the people of South Jakarta as many as 100 respondents from a population of 1,593,700 based on KPU data in 2016. The data analysis technique used is a regression. The results of this study showed that the stimulus-response theory tested through the hypothesis of media exposure provides a contribution (R Square: 27.6%) to increase the level of political participation. The results also support that online media, social media, and chatting applications were more often used as a source of political information compared to printed newspaper, radio, and magazines. Another finding of the research is that the level of online and strategic participation is still very low. Strategic participation can be improved when Internet users are encouraged to have the ability to operate a wide range of applications and have political knowledge. The research has also contributed to the development of online participation concept through instrumental, informative, and strategic dimensions.